Nasce uma estrela no Pampa Gaúcho: a crítica cinematográfica na Revista do Globo entre os anos de 1929 até 1950 - Araújo, Eduardo Barreto de (2023)
This thesis aims to present a discussion about cinema in Revista do Globo between the years 1929 to 1950. Born in the city of Porto Alegre and having its first issue published in 1929, this periodical circulated until 1967, when it ended its publications. activities. Owner of a modern visuality that dialogued with the urban context where it was inserted, it represented/presented not only the urban society of the capital of Rio Grande do Sul, but also of several other cities in the interior of Rio Grande do Sul. its existence issues related to the local, national and international context circulated through its pages. One of the subjects addressed in the pages of Revista do Globo was cinema. In many ways it occupied a space that was small at the beginning, but over the years it gained an important highlight. Having its own section within the structure of the journal. Based on the importance of cinema as a representation of reality, as a way of presenting social customs and reproducing cultural contexts. In this context, this thesis aimed to analyze the cinema section of Revista do Globo from a historical perspective, examining the reproduction of various aspects of the cinematographic universe. The general objective of the thesis, to analyze with the perspective of the historian the way in which the theme of cinema was reproduced in the pages of Revista do Globo was the great guiding element of the research. One of the specific objectives was to add information and contribute to an expansion of the historiography of cinema in Rio Grande do Sul and also, to a certain extent, in Brazil. Through characters who wrote for the magazine. These characters were part of the history not only of the periodical, but also of the arts in Rio Grande do Sul, thus contributing to a kind of group of intellectuals being formed and strengthened through the social and cultural practices that they maintained beyond the pages they wrote. about the movies. Finally, an attempt was made to present these intellectuals who wrote for the magazine and who contributed to the emergence of a specialized critique. If at the beginning they were seen by themselves as chroniclers, after a certain period they already considered themselves film critics and their contributions transcended the pages they wrote and created space for the emergence of study groups and the Clube de Cinema de Porto Alegre. Contributing to the expansion of these people's personal biography was also part of the research. It is expected from this thesis that elements may emerge for an expansion and consolidation of the historiography of cinema in Rio Grande do Sul.